Renewed Visions of the Historiography of Chiapas, 16th-20th Centuries - Fuentes Horta, Erick; Ledezma Díaz, Rafael Ángel (Revista de historia., 2022)
This issue integrates a set of articles on various issues and periods in the history of Chiapas. The seven articles and the documentary review were written by specialists in history and anthropology from Mexico and other countries. The texts cover various topics, regions and time periods: the encomiendas established in Ciudad Real —Los Altos region— in the mid-sixteenth century; changes in land use in the Indian villages of the Central Depression during the seventeenth and eighteenth centuries; the gradual disappearance of one of these villages —Escuintenango—; the philanthropic and scientific expeditions that arrived, first, to the Ciudad Real intendancy and then to the state of Chiapas in the 19th century; the labor relations that existed between enganchados and debtors in the coffee farms of Soconusco and, finally, the nationalist dynamics that were woven around the agrarian distribution in the border zone with Guatemala in the first half of the 20th century. These works qualify some commonplaces -still reproduced by academic and political sectors inside and outside Mexico- that minimize through simplistic readings the social and cultural complexity of the historical processes that defined the current reality of Chiapas. Therefore, the articles are part of that historiographical renewal that began in the 1980s and continues to this day despite the biased interpretations generated after the armed uprising of the Zapatista Army of National Liberation (EZLN) in 1994.